Electrochemical determination of free energy changes of allotropic transformation of ZnO - Kachhawaha J.S.; Tare V.B. (My University, 2025)
Partial and integral free energies of mixing of ZnO in single phase rock-salt solid solution of ZnO in NiO and CoO have been obtained in the temperature range 800 to 1000°C using electrochemical cells with calcia stabilized zirconia as solid electrolyte. The free energy of transformation of wurtzite ZnO to rock-salt ZnO, estimated from this thermodynamic data, is found to be 4,620 (±100) cal/mole at 900°C. Combining this value with the reported values for entropy changes, the enthalpy of transformation is estimated to be 4.150 (±335) cal/mole. © 1981.